SEMINAR CERDAS DIGITAL: (MENAVIGASI INFORMASI DAN MENCEGAH MISLEADING CONTENT, ARTIFICIAL INTELLEGENCE (AI) DAN KESENJANGAN SOSIAL) PERAN MAHASISWA KKN IAI SAHID BOGOR KELOMPOK 10 DALAM MENYAMPAIKAN PENTINGNYA MELEK BERDIGITAL BAGI PARA PELAJAR DI MA DAN - Aprilia; Shabila, Miranda; Widiyanti , Indri; Yanti, Novi; Kholilullah, Muhammad; Juliansyah, Muhamad Ednis; Sauri, Muhammad Sopian; Amalia, Intan Rahma (Lembaga Penelitan dan Pengabdian Masyarakat Institut Agama Islam Sahid, 2024)
In the rapidly evolving digital era, digital literacy is a crucial skill to manage the overwhelming flow of information, including the spread of fake news and misleading content. The KKN INAIS Bogor students, Group Desa Dukuh, organized a seminar titled “Smart Digital Literacy” at MA and MTs Darul Ihsan, Cibungbulang, Bogor, aimed at improving digital literacy among students. The objective of this seminar was to equip students with skills to navigate digital information, recognize characteristics of misleading content, and understand the benefits and risks of Artificial Intelligence (AI). The methods employed in this research included participatory observation, interviews with teachers and students, and an interactive seminar featuring hands-on training based on problem-based learning. Data were collected through pre- and post-seminar surveys to measure the improvement in students' understanding. The results showed a significant increase in the students' ability to recognize misleading content, verify information, and use AI responsibly. Before the seminar, only 20% of students could identify fake news, but this number increased to 75% after the seminar. The use of fact-checking tools also rose from 10% to 70% following the training. This seminar successfully enhanced the students' digital literacy and awareness of the importance of critical thinking and responsible technology use in the digital world.